The process of global indebtedness - Varga, József; Bánóczy, János; Gál, Veronika Alexandra; Sipiczki, Zoltán (Studia Mundi – Economica, 2022)
At the end of 2019, the world’s total debt was about 240 trillion. Governments, companies, households and banks are also in debt. The effects of major economic and political events can be seen in the process of indebtedness. The increase in indebtedness shows different trends in developed and emerging countries. There are a number of reasons for indebtedness. The final question is: is there a way out of the debt trap? In addition to the answers to this question by some experts (S. Gesell, I. Fisher, J. M. Keynes), we make two suggestions. The easier-to-implement version would allow the central bank to operate financially for development purposes by reinterpreting central bank independence. Our other proposal on the problem is to separate money creation and indebtedness. In our opinion, the unsustainable situation can be solved if government – with the help of the central bank – takes the issuance of money into its own hands.